Production of fertile sperm from in vitro propagating enriched spermatogonial stem cells of farmed catfish, Clarias batrachus. Issue 6 (15th July 2016) - Nayak, Swapnarani; Ferosekhan, Shajahan; Sahoo, Sangram Ketan; Sundaray, Jitendra Kumar; Jayasankar, Pallipuram; Barman, Hirak Kumar
Summary: Spermatogenesis is a highly co-ordinated and complex process. In vitro propagation of spermatogonial stem cells (SSCs) could provide an avenue in which to undertake in vivo studies of spermatogenesis. Very little information is known about the SSC biology of teleosts. In this study, collagenase-treated testicular cells of farmed catfish ( Clarias batrachus, popularly known as magur) were purified by Ficoll gradient centrifugation followed by magnetic activated cell sorting using Thy1.2 (CD90.2) antibody to enrich for the spermatogonial cell population. The sorted spermatogonial cells were counted and gave ~3 × 10 6 cells from 6 × 10 6 pre-sorted cells. The purified cells were cultured in vitro for >2 months in L-15 medium containing fetal bovine serum (10%), carp serum (1%) and other supplements. Microscopic observations depicted typical morphological SSC features, bearing a larger nuclear compartment (with visible perinuclear bodies) within a thin rim of cytoplasm. Cells proliferated in vitro forming clumps/colonies. mRNA expression profiling by qPCR documented that proliferating cells were Plzf + and Pou2 +, indicative of stem cells. From 60 days onwards of cultivation, the self-renewing population differentiated to produce spermatids (~6 × 10 7 on day 75). In vitro -produced sperm (2260 sperm/SSC) were free swimming in medium and hence motile (non-progressive) in nature. Of those, 2% were capable of fertilizing and generated healthy diploid fingerlings. Our documented evidence provides the basis for producing fertile magur sperm in vitro from cultured magur SSCs. Our established techniques of SSC propagation and in vitro sperm production together should trigger future in vivo experiments towards basic and applied biology research.